XALÍQTÍŃ TUWÍLÍWShÍLÍQ HÁM ÓLIMShILIK PROCESLERINE DEMOGRAFIYALÍQ KÓZQARAS - Utepova, G.B. (SCIENCE and SOCIETY, 2025)
This article evaluates birth rates and reproductive status, mortality and its influencing factors, as well as the conditions of average life expectancy from a demographic perspective.